Model Problem Based Learning Untuk Meningkatkan Hasil Belajar Fisika Peserta Didik - Rosmiati, Rosmiati; Maliq, Yusuf (Indonesian Journal of Pedagogical and Social Sciences, 2024)
Abstract. This classroom action research aims to improve the physics learning outcomes of class X.2 students at SMAN 1 Wonomulyo by applying the problem-based learning model. The research subjects were 35 class X.2 students. This classroom action research was carried out in two cycles with measurement material. Based on the results of descriptive analysis, it was found that the presentation of students' learning outcomes after being treated in each cycle had increased with the presentation in cycle I at 57.14% and cycle II at 77.14%. These results show an increase of 20% in students' physics learning outcomes after implementing the problem-based learning model in the learning process. Keywords: Problem Based Learning, Physics Learning Outcomes, Classroom Action Research